Improving Natural Science Learning Outcomes on the Topic of the Human Excretory System through Contextual Learning of Modeling Techniques for Grade VIII Students of SMP - Dwinaeni, Etik; Purwanto, Agus; Eskundari , Ratna Dewi (Journal of Biology Learning, 2023)
The objectives in this study were: 1) to improve learning activities in Natural Sciences in class VIII B students of SMP Warga Surakarta, 2) to improve learning outcomes, especially learning outcomes in Natural Sciences through contextual learning methods modeling techniques about the Human Excretory System in class VIII B students of SMP Warga Surakarta. The method used is action research method. The research was conducted on class VIII B students of SMP Warga Surakarta in the 2022/2023 academic year, as many as 27 students consisting of 13 boys and 14 girls. The data collection techniques were carried out by observing student and teacher activities, tests, partner teacher responses, and monitoring classroom observations. From the assessment test of Natural Science learning outcomes for each cycle of class action always increases, namely; the percentage of pre-cycle KKM achievement is 29.62%, cycle I is 44.44% and in cycle II it becomes 100%. Based on student responses in the implementation of learning using modeling techniques, it becomes more fun, easier to understand, makes students want to be more active and creative, students can find or interpret more freely, and is not confusing. So that by using the modeling method in learning Natural Sciences can help students in increasing activity and learning outcomes in Natural Sciences.